Reconstructing the Father’s Role in “Omar & Hana Arabic” Animation Series: The Importance of Fathers Involvement in Domestic Work - Shofi Najla Ufairoh; Muassomah Muassomah (MUWAZAH : jurnal kajian gender, 2024)
The animated series “Omar & Hana Arabic”, which is known as an Islamic educational show, presents a representation of father’s role that is different from patriarchal stereotypes. This research aims to 1) to identify the form of fathers involvement in domestic work; 2) to explain the impact of fathers involvement in domestic work. This research uses Qualitative with Qualitative Descriptive approach. The main source in this research is scenes and dialogs from the “Omar & Hana Arabic” animation series. Data collection was conducted through observation using three documentation techniques, namely watching, listening, and recording. The data were then analyzed according to the Miles and Huberman stage model which includes data reduction, data presentation, and conclusion drawing. The findings of this study illustrate that: 1) father is actively involved in the domestic sphere, namely childcare, such as reading inspirational stories to children, making children's toys, preparing children's meals, teaching children to ride bicycles, and playing with children. Father also contribute to household chores, such as caring for parents, washing dishes, folding clothes, preparing dinner for the family, cooking, shopping for home needs, and cleaning the house. 2) the involvement of fathers in childcare and household chores has three important impacts on the family: social impact for women (wife) because she has the opportunity to express herself; psychological impact for children when father have emotional closeness with his children; and cultural impact through the transmission of gender ideology that educates children that in the family, men and women have the same role and help each other.